A Kinetic Approach To The Definition Of Pathophysiology Of Low Antithrombin III (AT) Levels In Patients - Reeve, E B; Leonard, B D; Bies, R D; Ambruso, D R; Hathaway, W E (Thrombosis and Haemostasis, 1981)
Patients with 50 percent of normal levels of AT are at serious risk of deep venous thrombosis. Possible causes of 50 percent levels are (1) a halving of synthetic rate, or (2) a doubling of fractional catabolic rate. In health fractional catabolic rate is 50 percent of the plasma AT per day. Doubling of fractional catabolic rate-might be due to (a) the presence of a structurally defective AT molecule or (b) might be directly related to a great excess of AT consumption by complex formation with released clotting proteases. These possible causes of low AT levels can be distinguished by turnover studies with 131I-iabelled AT from the patient and from a healthy donor.We have developed simple, rapid methods of preparing highly purified AT from 30 to 60 ml of citrated blood and of labelling it with 131I without denaturation at about 0.5 iodine atom per AT molecule. A turnover study requires intravenous injection of 4-6 µC of 131I.Studies in a female patient with hereditary AT deficiency (40-50 percent AT level) compared to normal subjects indicates our approach. Fractional breakdown rate of her own 131l-AT was 50 percent per day indicating no obvious structural abnormality. Fractional breakdown rate of 131I_labelled donor AT was also 50 percent per day further indicating no difference in the behavior of her own and of normal AT and no excess consumption by clotting proteases. The patient's ability to compensate for increased AT-III consumption during an episode of thrombosis was impaired. Thus the patient suffered from a synthetic defect resulting in the ability to synthesize only 50 percent of her AT requirements per day.AT turnover studies provide an approach to the definition of the etiology of depressed AT levels in various disease states.